OPTIMALISASI PHP DAN MYSQL UNTUK SISTEM PEMETAAN POTENSI SEKOLAH MENENGAH KEJURUAN KOTA SEMARANG - Kristiawan Nugroho (AMIK Jakarta Teknologi Cipta Semarang, 2011)
On Duty Education of Town of Semarang have done mapping of school but not yet walked. because obtained data of schools still manually, this matter is caused by the the data not yet earned to be accessed to pass Computer because limitation of existing SDM, effect [of] all that presented data not yet accurate so that will have an in with intake of policy of service and head to society in forwarding of information concerning existence of school. System Mapping of Education of School specially SMK exist in Town of Semarang through computer technology will very useful because can be accessed to pass internet. To System society Mapping of Education of SMK will very useful because society can obtain; get information swiftly and easy to regarding pre-eminent products in SMK. Target of this researcher is expected will be able to assist to give elementary changes in order to facilitating presentation of data mapping of school through internet and can be accessed by society widely